JURIDICAL ANALYSIS OF THE EFFECTIVENESS OF IMMIGRATION REGULATIONS ON VISA ON ARRIVAL (VOA) 7 DAYS IN INCREASING FOREIGN TOURIST VISITS - Adek Dio Benardo; Lagat Parroha Patar Siadari; Siti Nurkhotijah (CV. Radja Publika, 2025)
The 7-day Visa on Arrival (VOA) policy is one of the innovations in Indonesia's immigration system aimed at increasing the number of foreign tourist visits, mainly in strategic border areas such as Batam City. The implementation of this policy is based on Government Regulation Number 45 of 2024 concerning PNBP, Circular Letter of the Director General of Immigration Number IMI-272. KU.01.03 of 2024, as well as the Decree of the Minister of Law and Human Rights Number M. HH-06.01.01 of 2023. Although normatively this policy already has a strong legal basis, the effectiveness of its implementation still needs to be studied comprehensively. This study aims to analyze the legal arrangements of the 7-day VOA policy from the perspective of immigration and tourism, evaluate its implementation in increasing foreign tourist visits to Batam City, and identify obstacles and provide solutions to improve the policy's effectiveness. The research methods used are normative and empirical juridical approaches, with data collection techniques through literature studies and field interviews at the Batam City Immigration Checkpoint. They also use socio-legal approaches and theoretical analysis from Lawrence M. Friedman and Soerjono Soekanto. The study results show that even though the 7-day VOA policy has been implemented administratively and has legitimate regulations, its implementation is still not optimal. The main obstacles are limited human resources, a lack of socialization, and low legal awareness among tourists. Therefore, it is necessary to strengthen the substance of policies, increase the capacity of the apparatus, integrate technology, and socialize with tourism industry players. Thus, this policy is expected to be not only normatively legal but also substantively effective in encouraging the growth of the national tourism sector